1990
DOI: 10.1073/pnas.87.18.7140
|View full text |Cite
|
Sign up to set email alerts
|

Trans-activation of HLA-DR gene by hepatitis B virus X gene product.

Abstract: (23) and is not expressed on normal human hepatocytes (24). Although aberrant expression of HLA-DR on hepatocytes observed during HBV infection has been suggested to be due to cytokines produced by the adjacent inflammatory cells (24, 25), it is not known whether HBV itself is involved in the induction process. This study demonstrates that transfection of cultured human hepatoma cell lines with genomic HBV sequences can induce HLA-DR expression in vitro in the absence of inflammation. We further show here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…In vitro, X exhibits a plethora of activities. From cell culture studies, it is believed that X can activate the transcription of host genes, including the major histocompatibility complex (94,219,251) and c-myc (4), as well as viral genes (37,192), and one investigator has even reported that X stabilizes viral RNAs (186). Most investigators agree that X is not a DNA binding protein and that it is therefore not a typical transactivator.…”
Section: Viral Proteinsmentioning
confidence: 99%
“…In vitro, X exhibits a plethora of activities. From cell culture studies, it is believed that X can activate the transcription of host genes, including the major histocompatibility complex (94,219,251) and c-myc (4), as well as viral genes (37,192), and one investigator has even reported that X stabilizes viral RNAs (186). Most investigators agree that X is not a DNA binding protein and that it is therefore not a typical transactivator.…”
Section: Viral Proteinsmentioning
confidence: 99%
“…One of the RNA polymerase III promoters is also transactivated by HBx (12). Several endogenous genes important for cell proliferation and acute inflammatory response, such as c-fos, c-jun, and human interleukin-8, are activated by HBx (3,7,13). This broad gene-regulating function suggests that HBx not only up-regulates the expression of HBV genes by transactivating the HBV enhancer but also modifies the environment by transactivating cellular genes in infected cells to facilitate viral replication.…”
mentioning
confidence: 99%
“…and cellular (10,23,27,47,56) Phosphorylation and dephosphorylation of c-Fos and c-Jun have been described as posttranslational modifications with a critical role in the regulation of AP1 function. Phosphorylation of the c-Fos C terminus seems to be important for negative autoregulation and for transformation (34,46) but not for transactivation of genes linked to an AP1 site.…”
mentioning
confidence: 99%
“…The hepatitis B virus (HBV) X gene encodes a polypeptide of 154 amino acids, with no significant homology with other known proteins, which is capable of transactivating gene expression acting on a wide spectrum of viral (13,28,42,49,55) and cellular (10,23,27,47,56) (8). Moreover, the relative promiscuity of its action suggests that the X protein acts indirectly, modifying the activities of cellular factors that modulate transcription from RNA polymerase II as well as from RNA polymerase III promoters (5,41).…”
mentioning
confidence: 99%